Theoretical aspects of developing the professional competence of future pre-conscription military education teachers - Mekhritdinovich, Uzoqov Asliddin (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to analyze the theoretical foundations and practical aspects of developing the professional competence of future pre-conscription military education teachers in Uzbekistan. It focuses on integrating national values and spiritual-moral education into military-pedagogical training to meet modern defense and societal needs. Research methodology: The research employed a qualitative conceptual approach supported by literature review, normative analysis, and comparative studies of domestic and international military didactics. It also involved analyzing national educational strategies and presidential decrees as the policy basis. Results: The study revealed that developing professional competence requires structured integration of moral education, military-professional motivation, and innovative didactic methods. It identified gaps between graduate competencies and qualification demands, highlighting the need for restructured curricula, improved training mechanisms, and modern pedagogical tools. Conclusions: The development of future military education teachers' competencies must be systematic, combining explicit and implicit learning models, aligned with national ideology and rapidly changing global challenges. A comprehensive approach improves not only educational outcomes but also students' readiness to serve the nation effectively. Limitations: The study focused on theoretical and policy-level analysis without empirical data collection, which may limit generalization to other educational systems or institutions. Contribution: This research contributes to educational theory by offering a model for integrating spiritual, professional, and practical training into military-pedagogical education, supporting national defense priorities and youth development in Uzbekistan.